Taxation of families and "families of taxation"? Inequality modification between family types across welfare states - Manuel Schechtl (Luxembourg Income Study (LIS), 2020)
Previous sociological research has overlooked the fact that a welfare state's tax system does not solely redistribute from rich to poor (vertical) but also between family types (horizontal). Different types of families are treated differently due to (de-)familialization policies in the tax code, such as joint filing for spouses or single-parent relief. In this study I aim to examine the tax system's modification of horizontal income inequality between the six most prevalent family types of non-retiree households. To answer my research aim I draw on harmonized data from 30 countries provided by the Luxembourg Income Study (LIS). I estimate pre- and post-fiscal income inequality measured as between-family-type Theil indices. Using linear regression, I examine the association of the percentage change in inequality and the prevalence of family type-related tax characteristics. I apply hierarchical cluster analysis to evaluate the congruence of welfare state classification and family tax policy. The results show that welfare states with familialization tax policies reduce less horizontal income inequality compared to welfare states without familialization tax policies. Nevertheless, the prevalence and outcomes of familialization policies in the tax code do not correspond to welfare state classifications.
Keywords: H23; H24; I38; 330; family; inequality; redistribution; social policy; taxation; welfare state